Debt Service of Low-Income Households in Indonesia - Laily Dwi Arsyianti; Irfan Syauqi Beik (Department of Islamic Economics, IPB University, 2015)
External source of fund is one way to get funds, but when it reaches 50 percent and above of disposable income, it becomes an issue. This paper attempts to elaborate determinants influencing low-income household in having 50 percent or more debt service ratio. By utilizing logistic regression approach to extract the data collected in the Greater Jakarta Indonesia, this study finds that when household head’s age is 45 years old and above, having 5 dependents or more, and is a home owner, the household is the most likely to have 50 percent and above debt service. While the least likely is when household head originally from Jakarta, no worry about future domestic economy condition, and have more than USD80 income per month. Variances of education level, marital status, occupation, financing institution, charity per income are not proved statistically significantly give effect to the variance of debt service in this study